The Influence of Environmental Performance, Green Accounting, and Profitability on Firm Value: A Study on Energy and Basic Materials Companies Listed on the IDX and Proper (2019-2023) - Bayu Dwi Cahyanto; Amir Indra Budiman (Journal Research of Social Science, Economics, and Management, 2025)
This study aims to determine the effect of environmental performance, green accounting, profitability on firm value with company size as a moderating variable for companies listed on the Indonesia Stock Exchange and PROPER from the Ministry of Environment and Forestry of the Republic of Indonesia for the period 2019 to 2023. The population of this study were 83 and 106 companies in the energy and basic material sectors, respectively, and obtained a sample of 28 companies based on the characteristics of this study. This research is quantitative research using the Partial Least Square (PLS) 3 analysis method. Based on the results of the study, it was found that Environmental Performance and Green Accounting has a positive and significant effect on Firm Value, while the Profitability Variable has no effect on Firm Value. The moderation test results show that company size strengthens the effect of environmental performance and green accounting on firm value, company size weakens the effect of profitability on firm value.